2023
DOI: 10.3390/molecules28052360
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Reactivity and Electronic Structure in Isorhodanine Derivatives Using Computer Simulations

Abstract: The electronic structure and reactivity of 22 isorhodanine (IsRd) derivatives in the Diels–Alder reaction with dimethyl maleate (DMm) were investigated under two different environments (gas phase and continuous solvent CH3COOH), using free Gibbs activation energy, free Gibbs reaction energy, and frontier molecular orbitals to analyze their reactivity. The results revealed both inverse electronic demand (IED) and normal electronic demand (NED) characteristics in the Diels–Alder reaction and also provided insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…It was also shown that the interaction energy between the cluster core and bipy ligands correlates linearly with the population of the V(Re, N in ) ELF basin. The behavior, when the basin population correlates with some bond related properties, is intuitive but does not have much confirmation in the literature [51][52][53]. Finally, since other members of the [Re 6 Q 8 L 4 X 2 ] (Q=S or Se; X=Cl or Br; L = 4,4 -bipyridine, 4-phenylpyridine) cluster family have a similar electronic structure to [Re 6 S 8 bipy 4 Cl 2 ], tendencies made in the current work can most likely also be applied to these compounds.…”
Section: Discussionmentioning
confidence: 90%
“…It was also shown that the interaction energy between the cluster core and bipy ligands correlates linearly with the population of the V(Re, N in ) ELF basin. The behavior, when the basin population correlates with some bond related properties, is intuitive but does not have much confirmation in the literature [51][52][53]. Finally, since other members of the [Re 6 Q 8 L 4 X 2 ] (Q=S or Se; X=Cl or Br; L = 4,4 -bipyridine, 4-phenylpyridine) cluster family have a similar electronic structure to [Re 6 S 8 bipy 4 Cl 2 ], tendencies made in the current work can most likely also be applied to these compounds.…”
Section: Discussionmentioning
confidence: 90%